Socially Responsive Performance Art: The History and Context of Selected Performance Art in Malaysia - Clara Ling Boon Ing; Sarena Abdullah (Wacana Seni Journal of Arts Discourse, 2023)
Since the 1990s, Malaysian artists have been using performance art as an artistic medium. Nevertheless, the history and context of performance art in Malaysia have not been examined in the context of Malaysian art history in particular. Coming from the fine arts background, artists such as Intan Rafiza, Sharon Chin, Aisyah Baharuddin, Rahmat Haron, Azizan Rahman Paiman, Mislina Mustaffa, and Fared Ayam, are among Malaysian artists who have been producing performance art as their main artistic medium. These performances, as will be discussed in this article, are what we define as “socially responsive medium” as these performances are not only ways for artists to express themselves but most importantly, the performances were inspired and executed as a form of artistic assertion or response in regard to various issues happening that triggered or inspired these artists to react via the execution of these performances. To give a better historical context and background, this article will first elucidate and delineate the historical development of performance art within the larger visual arts practice in Malaysia before focussing on the examination of selected performances by the few artists that this article argues as being “socially responsive.” This section will focus the term used and the nature of the performances itself.